2022
DOI: 10.3390/fire5030066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Severity of Wildfires on Some Physical-Chemical Soil Properties in a Humid Montane Scrublands Ecosystem in Southern Ecuador

Abstract: Humid montane scrublands (HMs) represent one of the least studied ecosystems in Ecuador, which in the last decade have been seriously threatened by the increase in wildfires. Our main objective was to evaluate the effects of wildfire severity on physicochemical soil properties in the HMs of southern Ecuador. For this purpose, fire severity was measured using the Normalized Burn Ratio (NBR) and the difference between pre-fire and post-fire (NBR Pre-fire-NBR Post-fire) over three contrasted periods (years 2019, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 66 publications
4
10
0
Order By: Relevance
“…The seasonality of fires that we documented during the 4 years contrasted (Fig. 4 ) is consistent with other studies in which many fires have been reported to be human-caused (Rother et al 2020 ; Carrión-Paladines et al 2022 ). However, in our study area due to the lack of information based on historical accounts (Crawford and Brueckheimer 2012 ) and limited fire records, we estimate that most of these events have an interannual occurrence trend.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The seasonality of fires that we documented during the 4 years contrasted (Fig. 4 ) is consistent with other studies in which many fires have been reported to be human-caused (Rother et al 2020 ; Carrión-Paladines et al 2022 ). However, in our study area due to the lack of information based on historical accounts (Crawford and Brueckheimer 2012 ) and limited fire records, we estimate that most of these events have an interannual occurrence trend.…”
Section: Discussionsupporting
confidence: 92%
“…The seasonality of fires that we documented during the 4 years contrasted (Fig. 4) is consistent with other studies in which many fires have been reported to be humancaused (Rother et al 2020;Carrión-Paladines et al 2022).…”
Section: Severity Of Traditional Burningsupporting
confidence: 92%
See 2 more Smart Citations
“…and pine ( Pinus radiata D. Don) plantations [ 4 , 5 , 6 ]. In addition, they face constant threats due to anthropogenic wildfires, which produce high and low severity fires, and the subsequent loss of soil quality due to erosion processes [ 7 ]. Despite being a highly anthropized ecosystem, the EMSs play an important role in the management of the micro-watersheds that supply drinking water to populations within Ecuador [ 8 ].…”
Section: Introductionmentioning
confidence: 99%